Feminist perspectives on transitional justice: from international and criminal to alternative forms of justice - Fineman, Martha; Zinsstag, Estelle (Series on transitional justice, 2013)
Introduction : feminist perspectives on transitional justice / Martha Albertson Fineman and Estelle Zinsstag -- International law and domestic gender justice, or why case studies matter / Catherin O'Rourke -- Advancing a feminist analysis of transitional justice / Fionnuala Ní Aoláin -- Feminist perspectives on extraordinary justice / David C. Gray and Benjamin A. Levin --Intersectionality : a feminist theory for transitional justice / Eilish Rooney -- International law, crisis and feminist time / Mary H. Hansel -- Justice as practised by victims of conflict: post-World War II movements as sites of engagement and knowledge / Cheah Wui Ling -- The symbolic and communicative function of International Criminal Tribunals / Teresa Godwin Phelps -- Sexual violence against women in armed conflicts and restorative justice : an exploratory analysis / Estelle Zinsstag -- Greensboro and beyond : remediating the structural sexism in truth and reconciliation processes and determining the potential impact and benefits of truth process in the United States / Peggy Maisel -- Exclusion of women in post-conflict peace processes: transitional justice in Northern Uganda / Joseph Wasonga -- Shifting paradigms for state intervention: gender-based violence in Cuba / Deborah M. Weissman -- Beauty and the beast : gender integration and the police in post-conflict Bosnia and Herzegovina / Lisa R. Muftić and Azra Rašić -- The parallel processes of law and social change : gender violence and work in the United States and South Africa / Julie Godlscheid -- Neoliberalism's impact on women : a case study in creating supply and demand for human trafficking / Dina Francesca Haynes